Financial variables and macroeconomic forecast errors - Michelle L. Barnes; Giovanni P. Olivei (Federal Reserve Bank of Boston, 2017)
A large set of financial variables has only limited power to predict a latent factor common to the year-ahead forecast errors for real Gross Domestic Product (GDP) growth, the unemployment rate, and Consumer Price Index (CPI) inflation for three sets of professional forecasters: the Federal Reserve's Greenbook, the Survey of Professional Forecasters (SPF), and the Blue Chip Consensus Forecasts. Even when a financial variable appears to be fairly robust across sample periods in explaining the latent factor, from an economic standpoint its contribution appears modest. Still, several financial variables retain economic significance over certain subsamples; when non-linear effects are accounted for, these variables have an improved ability to consistently predict the latent factor over the business cycle.
Keywords: C24; C53; C55; E37; E44; E50; G01; G17; 330; Forecast errors; macroeconomy; financial variables; threshold estimation; business cycle